(untitled) (International Journal of Engineering and Computer Science, 2017)
In VANET for the purpose of saftey, vehicles need to periodically broadcast safety messages providing precise position information to nearby vehicles. However, this frequent messaging (e.g., every 100 to 300ms per car) greatly facilitates the tracking of vehicles, as it success to eavesdrop the wireless medium. As a result, the driver’s privacy can’t be protected. In order to protect personal location information we proposes the mix zone concept. Cryptographic Mix (CMIX) protocol is used here to improve location privacy of Mix-Zone. We propose to do so using pseudonym changes and cryptography. The paper is concluded with an investigation based on current results of upcoming elements to be integrated in our secure VC architecture.